Diagnostics for typhoid fever: current perspectives and future outlooks for product development and access - Sapkota, J; Roberts, T; Basnyat, B; Baker, S; Hampton, LM; Dittrich, S (Oxford University Press, 2023)
Typhoid is an enteric disease caused by Salmonella Typhi. Like many febrile illnesses, typhoid presents with nonspecific symptoms. In routine healthcare settings in low- and middle-income countries, typhoid fever is suspected and treated empirically. Though many diagnostic tests are available for typhoid diagnosis, there are currently no diagnostic tests that meet ideal requirements for sensitivity, specificity, speed, and cost-effectiveness. With introduction of typhoid conjugate vaccine, it is essential to explore the current and future typhoid approach in the context of use case and access to ensure their utilization for disease control.